Common spatial patterns of trees in various tropical forests: Small trees are associated with increased diversity at small spatial scales. Issue 12 (27th May 2021) - Fibich, Pavel; Novotný, Vojtěch; Ediriweera, Sisira; Gunatilleke, Savitri; Gunatilleke, Nimal; Molem, Kenneth; Weiblen, George D.; Lepš, Jan
Abstract: Tropical forests are notable for their high species diversity, even on small spatial scales, and right‐skewed species and size abundance distributions. The role of individual species as drivers of the spatial organization of diversity in these forests has been explained by several hypotheses and processes, for example, stochastic dilution, negative density dependence, or gap dynamics. These processes leave a signature in spatial distribution of small trees, particularly in the vicinity of large trees, likely having stronger effects on their neighbors. We are exploring species diversity patterns within the framework of various diversity‐generating hypotheses using individual species–area relationships. We used the data from three tropical forest plots (Wanang—Papua New Guinea, Barro Colorado Island—Panama, and Sinharaja—Sri Lanka) and included also the saplings (DBH ≥ 1 cm). Resulting cross‐size patterns of species richness and evenness reflect the dynamics of saplings affected by the distribution of large trees. When all individuals with DBH ≥1 cm are included, ~50% of all tree species from the 25‐ or 50‐ha plot can be found within 35 m radius of an individual tree. For all trees, 72%–78% of species were identified as species richness accumulators, having more species present in their surroundings than expected by null models. This pattern was driven by small trees as the analysis of DBH >10 cm trees showed much lower proportion of accumulators, 14%–65% of species identified as richness repellers and had low richness of surrounding small trees. Only 11%–26% of species had lower species evenness than was expected by null models. High proportions of species richness accumulators were probably due to gap dynamics and support Janzen–Connell hypothesis driven by competition or top‐down control by pathogens and herbivores. Observed species diversity patterns show the importance of including small tree size classes in analyses of the spatial organization of diversity. Abstract : Common spatial patterns of trees were observed in three tropical forest plots. Small trees were associated with increased diversity, while large trees were more often associated with low diversity. Gap dynamics and negative density‐dependent processes were expected to form the diversity patterns.